Biomass-modulated fire dynamics during the last glacial-interglacial transition at the Central Pyrenees (Spain) - Gil-Romera, Graciela; González-Sampériz, Penélope; Lasheras-Álvarez, Laura; Sevilla-Callejo, Miguel; Moreno, Ana; Valero-Garcés, Blas; López-Merino, Lourdes; Carrión, José S; Pérez Sanz, Ana; Aranbarri, Josu; García-Prieto Fronce, Eduardo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2014)
Understanding long-term fire ecology is essential for current day interpretation of ecosystem fire responses. However palaeoecology of fire is still poorly understood, especially at high-altitude mountain environments, despite the fact that these are fire-sensitive ecosystems and their resilience might be affected by changing fire regimes. We reconstruct wildfire occurrence since the Lateglacial (14.7calka BP) to the Mid-Holocene (6calka BP) and investigate the climate–fuel–fire relationships in a sedimentary sequence located at the treeline in the Central Spanish Pyrenees. Pollen, macro- and micro-charcoal were analysed for the identification of fire events (FE) in order to detect vegetation post-fire response and to define biomass–fire interactions. mean fire intervals (mfi) reduced since the Lateglacial, peaking at 9–7.7calka BP while from 7.7 to 6calka BP no fire is recorded. We hypothesise that Early Holocene maximum summer insolation, as climate forcing, and mesophyte forest expansion, as a fuel-creating factor, were responsible for accelerating fire occurrence in the Central Pyrenees treeline. We also found that fire had long-lasting negative effects on most of the treeline plant communities and that forest contraction from 7.7calka BP is likely linked to the ecosystem's threshold response to high fire frequencies.
Keywords: Fire history; historical biogeography; iberian peninsula; l Palaeoecology; Lateglacia; quaternary

Rapid climatic changes and resilient vegetation during the Lateglacial and Holocene in a continental region of south-western Europe - Aranbarri, Josu; González-Sampériz, Penélope; Valero-Garcés, Blas; Moreno, Ana; Gil-Romera, Graciela; Sevilla-Callejo, Miguel; García-Prieto, Eduardo; Di Rita, Federico; Mata, M. Pilar; Morellón, Mario; Magri, Donatella; Rodríguez-Lázaro, Julio; et al. (Global and Planetary Change, 2014)
Palynological, sedimentological and geochemical analyses performed on the Villarquemado paleolake sequence (987m a.s.l, 40°30′N; 1°18′W) reveal the vegetation dynamics and climate variability in continental Iberia over the last 13,500calyrBP. The Lateglacial and early Holocene periods are characterized by arid conditions with a stable landscape dominated by pinewoods and steppe until ca. 7780calyrBP, despite sedimentological evidence for large paleohydrological fluctuations in the paleolake. The most humid phase occurred between ca. 7780 and 5000calyrBP and was characterized by the maximum spread of mesophytes (e.g., Betula, Corylus, Quercus faginea type), the expansion of a mixed Mediterranean oak woodland with evergreen Quercus as dominant forest communities and more frequent higher lake level periods. The return of a dense pinewood synchronous with the depletion of mesophytes characterizes the mid-late Holocene transition (ca. 5000calyrBP) most likely as a consequence of an increasing aridity that coincides with the reappearance of a shallow, carbonate wetland environment. The paleohydrological and vegetation evolution shows similarities with other continental Mediterranean areas of Iberia and demonstrates a marked resilience of terrestrial vegetation and gradual responses to millennial-scale climate fluctuations. Human impact is negligible until the Ibero-Roman period (ca. 2500calyrBP) when a major deforestation occurred in the nearby pine forest. The last 1500years are characterized by increasing landscape management, mainly associated with grazing practices shaping the current landscape.
Keywords: aridity; Continental Iberia; Holocene; Multiproxy reconstructio; Pinewoods; Vegetation resilience

Expected trends and surprises in the Lateglacial and Holocene vegetation history of the Iberian Peninsula and Balearic Islands - Carrión, José S.; Fernández, Santiago; González-Sampériz, Penélope; Gil-Romera, Graciela; Badal, Ernestina; Carrión-Marco, Yolanda; López-Merino, Lourdes; López-Sáez, José a; Fierro, Elena; Burjachs, Francesc (Review of Palaeobotany and Palynology, 2010)
Recent, high-resolution palaeoecological records are changing the traditional picture of post-glacial vegetation succession in the Iberian Peninsula. In addition to the inﬂuence of Lateglacial and Early Holocene climatic changes, other factors are critical in the course of vegetation development and we observe strong regional differences. The ﬂoristic composition, location and structure of glacial tree populations and communities may have been primary causes of vegetation development. Refugial populations in the Baetic cordilleras would have been a source, but not the only one, for the early Lateglacial oak expansions. From Mid to Late Holocene, inertial, resilient, and rapid responses of vegetation to climatic change are described, and regional differences in the response are stressed. The role of ﬁre, pastoralism, agriculture, and other anthropogenic disturbances (such as mining), during the Copper, Bronze, Iberian, and Roman times, is analysed. The implications of ecological transitions in cultural changes, especially when they occur as societal collapses, are discussed.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Holocene; iberia; palaeobotany; palaeoecology; palaeogeography; quaternary